A new genus of the weevil subfamily Lixinae (Coleoptera: Curculionidae) from Arabian peninsula - Yu.G. Arzanov (Кавказский энтомологический бюллетень, 2009)
On materials of collection ZIN RAS (Saint Petersburg) from Arabian peninsula new genus Arabocleonus gen. n. with typical species Arabocleonus medvedevi sp. n. is described. Position of a new genus is not absolutely clear yet in system trybus Cleonini. The new genus on appearance and colouring reminds some species from genera Pachycerus Schoenherr, 1823, Bothynoderes Schoenherr, 1823, Cosmogaster Faust, 1904 and Neocleonus Chevrolat, 1873, but differs from them a structure rostrum, eyes, tarsus and one-topmost baso-dorsal a ledge internal sac, and also rudiments of felt soles and scales top elytron.